Detection of inversion with breakpoints in ARSB causing MPS VI by whole-genome sequencing: lessons learned and best practices - Huang, Yufeng; Deng, Wenyue; Huang, Hui; Zhang, Xiankai; Chen, Xiaohong; Ye, Jian; Luo, Sukun; Yu, Ting; Yao, Hui; Du, Hao; He, Xuelian (Frontiers in Genetics, 2025)
IntroductionMucopolysaccharidosis type VI (MPSVI), an autosomal recessive lysosomal storage disorder caused by pathogenic variants in ARSB gene. Usually, whole exome sequencing (WES) can identify these variants, and if WES failed to detect causative variants, whole-genome sequencing (WGS) may be considered to investigate deep intronic variations and structural alterations in patients.MethodsWhole-exome sequencing (WES) and whole genome sequencing (WGS) were performed in a Chinese family having a boy with suspected diagnosis of MPS with macrocephaly, coarse facial features, broad forehead, thick lips, frontal bossing, craniosynostosis, blue spots, frequent upper respiratory infections, inguinal hernia, and dysostosis multiplex. Lysosomal enzymatic assays for leucocytes were used to assess the activity of arylsulfatase B of the boy’s leucocytes. Sanger sequencing and karyotyping analysis were used to validate the variants identified in the boy and his parents.ResultsThis boy diagnosed with MPSVI based on clinical phenotypes and laboratory biochemical assays, and WES identified only a maternally inherited missense variant, c.908G>T (p.Gly303Val), in the ARSB gene. By performing WGS, we found a paracentric inversion involving chromosome 5q14.1q13.2 (78180730-138771424 inv), disrupting the ARSB gene on the proband and his father. The inversion was confirmed through karyotyping analysis, and the breakpoints were validated by agarose gel electrophoresis and Sanger sequencing.DisscussionThis study reminds us that WGS should be done when WES failed to achieve a molecular diagonosis, and it also underscores the importance of WGS especially in cases of high clinical suspicion.